Dissemination of Pt-Ir k-112 mass measurement standards to E0-74 working standards with sub-divisional methods - Zuhdi Ismail; Renanta Hayu Kresiani (Journal of Physics: Theories and Applications, 2022)
The mass value of the weights that are the mass unit's standard must be determined correctly, especially for E0 no 74 as the national working standard. Sub-division is the method commonly used to determine the mass of these weights. The sub-division method involved three standard weights in this study, namely Pt-Ir K-112, E0 no 74, and E0 no 75. Pt-Ir was used as the measuring standard, while the E0 class weights were test weights and check standard. The mass value of both weights was determined based on the mass value of Pt-Ir, which was analyzed using the weighted least squares method. The calibration obtained that the mass values of E0 no 74 and E0 no 75 were 1000,000046 g and 1000,000163 g, respectively. In measurement, the uncertainty value becomes a very important part of being stated. The uncertainty obtained for both E0 weights is 0.036 mg.